Cover Picture: Perspectives on liquid biopsy for label‐free detection of "circulating tumor cells" through intelligent lab‐on‐chips (View 3/2020). Issue 3 (22nd September 2020) - Miccio, Lisa; Cimmino, Flora; Kurelac, Ivana; Villone, Massimiliano M.; Bianco, Vittorio; Memmolo, Pasquale; Merola, Francesco; Mugnano, Martina; Capasso, Mario; Iolascon, Achille; Maffettone, Pier Luca; Ferraro, Pietro
Abstract : In article number 20200034, Pietro Ferraro and co‐workers emphasize that early detection in cancer diseases is a key issue. The current state of the art of technology could allow a great opportunity for this purpose, to develop systems for detecting circulating cancer cells (CTC) in the blood. The challenge is to recognize and classify cancer cells and detect them non‐invasively through a lab‐on‐chip device as they flow. Single‐cell holographic phase contrast tomography offers the possibility in the real world to detect CTC in a label‐free mode by means of morphological analyzes when combined with artificial intelligence (AI). The cover summarizes and depicts the main concepts and the technological ingredients necessary to achieve such an ambitious goal, namely the recognition and sorting of cells, 3D‐imaging by microscope and complete morphological analysis of 3D‐phase‐contrast tomograms by AI tools.